Rancangan Platform Pembelajaran Sejarah Lokal Berbasis Gamifikasi untuk Meningkatkan Keterlibatan Siswa di Era Digital - Agung Dwi Kurniawan; Aisyah Nurfadillah Adien; Eva Fauziah (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
History lessons play an important role in shaping students' character and national identity, including awareness of local history. However, in practice, history learning, especially local history, is still less popular because the presentation tends to be monotonous and based on memorization. This study aims to design a gamification-based online learning platform that can increase students' interest in learning local history in a more interactive and enjoyable way. The study used the Research and Development (R&D) method which focused on the design stage. The design results show that the characteristics of an effective platform include the integration of gamification elements such as points, badges, leaderboards, and reward and penalty systems through the "lives" and "diamond" features. In addition, the presentation of the material is done visually through interactive videos that can be accessed based on certain levels. This platform is also equipped with a gallery page, leaderboard, and virtual store to support continuous learning motivation. With this approach, it is hoped that students will not only be interested in learning local history, but also gain a deeper and contextual understanding in learning local history. This platform is an innovative solution in history learning that is adaptive to the needs of the digital generation and is able to bridge technology with education based on local cultural values.